Validity and Reliability of Test and Non-Test Research Instruments on Chemical Bond Materials - Riswana, Syah Nurul; Nasution, Haqqi Annazili (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This research aims to determine the feasibility of research instruments through the validity and reliability of test and non-test instruments on chemical bonding materials. The instruments tested were in the form of multiple-choice questions, and the non-test instruments were in the form of questionnaires. Validity and reliability testing aims to determine the suitability of the test instrument. The test instruments aim to measure learning outcomes, and the non-test instruments aim to measure students' motivation for chemical bonding material. Validity and reliability testing of the test instrument was carried out by testing content validity with expert validators and small-scale field trials with students in class XI Science 1 at SMA Negeri 14 Medan. Non-test instrument testing was carried out through content validation tests on three expert validators. The research results showed that of the 40 questions, there were 28 valid questions, and the reliability test obtained r-11 = 0.85 and was included in the high reliability category. At the difficulty level of the questions, the number of questions in the difficult category was 5; 24 in the medium category; and 11 in the easy category. Then, regarding the differentiating power of questions in the good category, the number obtained was 25, and in the bad category, the number obtained was 15. The percentage of eligibility for non-test instruments obtained was 90%, which is a feasible criterion.